منهج القرآن الكريم في تحقيق الأمن الأجتماعي في أفغانستان : دراسة تحليلية - عبد الرشيد، محمد أنور (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research is an analytical study that investigates the methodology of the holy Quran in targeting social security issues in Afghanistan. This study is expected to be a significant addition to the available literature. It provides a comprehensive Quranic solution towards achieving social security in a geographical area that suffers from the lack thereof more than any other Islamic world region. The survival of mankind is based on attaining social security, which is one of the Quran's most important objectives. The Quranic methodology provides the best rules, foundations, and standards, ensuring security in society. The study discusses social security from both contemporary and Shari'ah perspective. It provides a detailed discussion on the essential elements of social security, such as its moral, practical, and social components. It also provides an overview of Afghanistan's historical, geographical, and political situation and the extent to which social security prevails in the country. The study is supported by accurate statistics as well as ground realities witnessed in Afghanistan. The study focuses on the most important gaps in Afghan society that threaten to destabilize its social security. Among the gaps are a) family obstacles such as difficulty in building a family, a high percentage of divorce, and deprivation of women from inheritance; b) social obstacles such as extremism in nationalism, tribal loyalties, the negative role played by an undisciplined and largely unregulated media, and the unbridled proliferation of drugs. The study has adopted the inductive and analytical research methods to analyze data collected from the Quran and Sunnah and Afghan society's characteristics. Quranic verses and Hadith that call for upholding ethical values, solidarity amongst societal members, adoption of legislation sanctions, and other good social standards were used to infer the true Quranic approach that would lead to lasting social security in Afghanistan. Consequently, this study highlights a set of Quranic solutions that can address these obstacles by strengthening societal norms' religious and ethical aspects. This study found that a) the family institution is a fundamental factor of social security in Afghan society, in terms of its formation and learning, b) upholding the law and the constructive role of authorities are essential in helping to achieve social security, c) the correct treatment of donation (Sadaqah) and Zakah money by rightfully treating it as a divine duty motivates individual members of society in playing their roles towards achieving social solidarity, and d) instigating hope in and awakening the consciences of drug users can act as the most beneficial medicine that would help to eliminate drug use from society, in addition to local and international efforts towards its eradication. In conclusion, there is no doubt that following these divine Quranic injunctions and methodologies would help to bring lasting social security to Afghan society.